Nematodes Parasitizing Hops in Florida - Johan Desaeger (EDIS, 2019)
The rapid growth of Florida's craft beer industry has created new opportunities for Florida growers to introduce and establish commercial hop (Humulus lupulus) operations. This new industry would have the potential to provide new and high profitable markets for Florida growers. However, many challenges make the establishment of this industry difficult.  They include limited knowledge of cultivars suitable to Florida’s climatic conditions, and lack of information on potential pests and diseases that will affect adversely this crop in Florida.